Generalizzare, proiettare, evitare i gesti incompleti come strumento di analisi psicologica (Lebenswelt. Aesthetics and philosophy of experience., 2019)
This article aims to apply the classification of incomplete gestures introduced by Maddalena (2015) as a tool for understanding and classifying different attachment patterns (West 2001; Ainsworth, Blehar, Waters, Wall 1978; Talia, Miller-Bottome, Daniel 2017). In the first section the classification of incomplete gestures proposed by Maddalena will be reconstructed. In the second part the relationship between communication and attachment will be introduced through a brief critical survey of the psychological literature dedicated to this subject. In the third part I aim to show how the specific communication of the insecure avoidant pattern is characterized by two specific types of incomplete gestures: schematization and projection. Specifically, the avoidant seems to adopt communicative strategies that allow to minimize, deactivate or at least limit the conjunction between the two phenomenological qualities of firstness and secondness (Peirce). In the conclusions, I will briefly analyse some theoretical repercussions of the approach adopted, especially with regard to the relationship between incompleteness and completeness.